Latent Hybridity in Administrative Crisis Management: The German Refugee Crisis of 2015/16. (13th October 2020) - Eckhard, Steffen; Lenz, Alexa; Seibel, Wolfgang; Roth, Florian; Fatke, Matthias
Abstract: Studying the so-called refugee crisis in Germany, this article asks about the effectiveness of crisis management by a large number of local administrations, each acting upon the same crisis impulse of a high number of asylum seekers who entered the country in 2015 and 2016. Instead of theorizing the exact administrative design features fit for an effective crisis response, the focus is on the ability of administrations to adjust. We conceptualize such shifts in administrative practices as informal and temporary (latent) deviations from routine action along two dimensions of organizational behavior typically dominant in private and nonprofit sector organizations, respectively: internal flexibility and citizen participation (hybridity). Novel survey data from 235 out of 401 German district authorities are reported. We test the effects of different forms of latent hybridization on administrative effectiveness using regression modeling. Findings indicate that changes in administrative practices towards more flexible and participatory action had a positive impact on self-reported crisis management effectiveness. The effect of flexible action was especially pronounced in districts that were allocated higher shares of asylum seekers. These findings advance theory on crisis management and bottom-up implementation, highlighting the ability of local agencies to shift practices as a key explanatory factor for effective administrative action in exceptional situations.